2022
DOI: 10.2298/jas2202203t
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods for the detection of Phytophthora infestans on potatoes in Mauritius

Abstract: Late blight, a disease caused by oomycota, Phytophthora infestans, is a greater threat to the potato crop than any other disease in Mauritius. This disease remains the most challenging to manage once symptoms have appeared, thus requiring rapid detection for effective disease management. The aim of this study was to compare different methods for early detection of the causal agent of potato late blight. Conventional culture-based methods involved the direct isolation of P. infestans from infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Accession numbers obtained from the NCBI GenBank for each isolate are listed in (Table 1). It has been shown that, depending on the genotype, P. infestans cultures can be kept alive for at least a year [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accession numbers obtained from the NCBI GenBank for each isolate are listed in (Table 1). It has been shown that, depending on the genotype, P. infestans cultures can be kept alive for at least a year [17].…”
Section: Resultsmentioning
confidence: 99%
“…While all Phytophthora species grow well on oatmeal agar, the medium is dense and opaque [16]. Most Phytophthora strains are unable to produce sporangia or develop oospores on potato dextrose agar (PDA) [17,18]. In a preliminary screen [6], the components of locally accessible rye agar media for P. infestans culture were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…After 7 days of incubation, fungal isolates presumptively identified on PDA were selected for molecular identification. Briefly, mycelial growth was scraped from the plate, weighed, and ground with liquid nitrogen (Takooree et al, 2022). DNA was extracted by the Cetyl Trimethyl Ammonium Bromide (CTAB) method (Madarbokus and presumptively.…”
Section: Molecular Characterisation Of the Etiological Agent Of Disea...mentioning
confidence: 99%